Photodegradation of Metamifop in the Presence of Fe(II) Ions - Rosli, Muhamad Izzat (2016)
Photodegradation, one of the Advanced Oxidation Process (AOP) is widely used as a promising method in water treatment industry. The photodegradation process was implemented using UV light to initiate the production of effective hydroxyl radicals (•OH) to degrade the targeted pollutant like pesticides, herbicides and other pollutant compounds. In spite of that, the treatment process could be affected with the presence of Fe(II) ions , which is among the commonly found heavy metal pollutant from surface water. Consequently, the photodegradation of herbicide namely metamifop with the presence of Fe(II) ions in aqueous solution was conducted in this study. This experiment was conducted in two different concentration of metamifop solution (sample) which were 5 ppm and 10 ppm. Each sample (5 ppm and 10 ppm of metamifop solution) were evaluated in the absence and presence (5 ppm and 10 ppm) of Fe(II) ions. The result showed that the metamifop degradation percentage was lower in the absence of Fe(II) ions. It was recognized that in 5 ppm of metamifop solution, the degradation percentage in the absence of Fe(II) ions was 16.57% whereas the presence of Fe(II) ions has increased to 34.55% (5 ppm of Fe(II) ions) and 53.89% (10 ppm of Fe(II) ions). In 10 ppm of metamifop solution, 8.68% of degradation has been detected in the absence of Fe(II) ions while the presence of Fe(II) ions resulted 18.11% (5 ppm of Fe(II) ions) and 41.76% of degradation (10 ppm of Fe(II) ions). The result showed that the degradation of metamifop increased by increasing the Fe(II) ions concentration.